Natural sensitizers-mesoporous TiO2 hybrid nanomaterial for future optoelectronic applications - Nitasha Chaudhari; Swapnali Walake; Yogesh Hase; Paresh Nasikkar; Sandesh Jadkar; Yogesh Jadhav; Atul Kulkarni (Journal of Experimental Nanoscience, 2023)
Optoelectronics deals with the design and development of electronic devices including photodetector (PD), solar cells and LEDs for light detection, generation and application for a variety of purposes. It includes X-rays, Gamma rays, Infrared, Ultraviolet and Visible light. In the current work, we developed a self-powered and efficient UV–Visible PD by sensitizing mesoporous TiO2 powder with a natural sensitizer Ficus Benghalensis (Banyan) and Rubia Cordifolia (Manjishtha). Prominent enhancement of visible light absorption was noted due to sensitizers as compared to pure TiO2 with the decrease in band gap from 3.13 eV to 3.01 eV. TiO2 photoanodes fabricated with and without dye loading were characterized using XRD, FESEM and UV–Visible and FTIR spectroscopy and used to fabricate a PD device with an active area of 0. 25 cm2. At zero bias, the Banyan-loaded TiO2 PD (B-TiO2) demonstrates enhanced photo response by nearly three times than Manjishtha-loaded PD (M-TiO2). At zero bias voltage, the PD (B-TiO2) displayed very high photosensitivity (8665), Dark current density (126 nA), Photocurrent density (158 µA), Photoresponsivity (1.88 mA/W), Rise time (0.31S) and Decay time (0.35S), respectively. Therefore, the use of novel dye for electricity generation in this study opens new routes to design future optoelectronics devices.